International Codification: Challenges and Perils - Keith, KJ (Victoria University of Wellington Law Review, 2023)
This tribute to Professor Emeritus Tony Smith considers the codification of international law, particularly international criminal law, given Tony's long-term commitment to criminal law. It also evaluates the codification of international law in other areas, addressing success and failure.